Enhanced performances of cement and powder silane based waterproof mortar modified by nucleation C-S-H seed. (20th June 2020) - Li, Haoxin; Xu, Chao; Dong, Biqin; Chen, Qing; Gu, Linan; Yang, Xiaojie
Highlights: It significantly increases the strengths and anti-penetration capacity. It reduces the water capillary absorption and drying shrinkage. It slightly affects chemical shrinkage and significantly reduces pores volumes. It promotes the early hydration of waterproof paste. Abstract: Aimed to enhance the performance of the cement and powder silane water repellent based waterproof mortar, different contents of nucleation C-S-H seed were thus introduced into various mortars and pastes, their performances such as strengths, water capillary absorptions, anti-penetration capacities, drying shrinkages and chemical shrinkages were evaluated. The pore size distributions of hardened mortars, heat liberations and crystalline phases of pastes cured for different ages were also measured to explore the mechanisms which are responsible for the enhanced performances. The results indicate that the nucleation C-S-H seed significantly increases the strengths and anti-penetration capacity, reduces the water capillary absorption and drying shrinkage of the waterproof mortar. It slightly affects the chemical shrinkage, but significantly reduces the volumes of the pores, especially the gel and large capillary pores. Overall, it promotes the early hydration of the cement and powder silane paste. It accelerates the conversion of ettringite (AFt) to monosulfoaluminate (AFm) and increases calcium hydroxide (CH) content in the hardened paste cured for 3d. It cuts down the entering time of acceleration period and the contents of un-hydrated clinker phases such as tricalcium silicate (C3 S) and dicalcium silicate (C2 S). These results will provide a theoretical reference for the preparation of cement and powder silane based waterproof mortar with better performances.